PENGARUH MIKOTOKSIN DALAM PAKAN TERHADAP PRODUKSI AYAM PETELUR KOMERSIAL DI PENATARAN FARM, WILAYAH KABUPATEN BLITAR - , Nugroho Budiono, Prof. drh. Charles Rangga Tabbu,M. Sc., Ph. D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was designed to evaluate the types and levels of mycotoxins in feedâs raw materials and complete feeds of commercial layers and their effects on egg production. This research was done in Penataran farm at the District of Blitar, which is a commercial layer farm of 18,000 hens. Samples of feedâs raw materials that have been examined, included rice bran, corns, soybean meal (SBM), corn gluten meal (CGM), dried destillers grain with solubleâs (DDGS), and complete feed samples from the storage and feed left over. Examination of the types and levels of mycotoxins was done by the method of high performance liquid chromatography (HPLC) at Romers Laboratory, Singapore. Observation on the egg production of the group of chickens received mycotoxins contaminated feed was done at the age of 19 weeks, 26 weeks, and 35 weeks. Evaluation was done on the percentage of egg production, egg weight, egg shell quality, and egg albumin as well as egg yolk quality. Evaluation on the possibility of immunosuppresive effect was based on examination of the antibody titer against Newcastle disease virus (NDV) was done at the age of 19 weeks, 26 weeks, and 35 weeks using 30 blood samples of chickens from each period. The results indicated that all feedâs raw materials and complete feed are contaminated by mycotoxins, include aflatoxin B1, deoxynivalenol (DON), fumonisin B1, ochratoxin A, and zearalenone. The highest level of aflatoxin A in feedâs raw materials was detected in ground corn (68 Âµg/kg), and the lowest was found in un-ground corn, SBM, and DDGS (< 1 Âµg/kg). The highest level of DON was detected in DDGS (<198 Âµg/kg), and the lowest was observed in SBM and rice bran (<50 Âµg/kg). The highest level of fumonisin B1 was detected in CGM (2583 Âµg/kg, and the lowest was found in SBM (<100 Âµg/kg). The highest level of ochratoxin A was observed in CGM (14,2 Âµg/kg), and the lowest was found in unground corn, ground corn, DDGS, and rice bran (<0.5 Âµg/kg). The highest level of zearalenone was detected in CGM (319 Âµg/kg), and the lowest was found in SBM (<10 Âµg/kg). Contamination of feed with mycotoxins caused a lower hen house egg production (HHEP) of 0.4 kg/hen, lower egg production and egg weight compared to the Standard Breed. Eggs produced have variable size, and showed pale, thin, soft, or cracked shell, watery albumin, and pale yolk. The antibody titer against NDV was low at the group of 19 weeks of age, very high due to NDV field challenge at the group of 26 weeks of age, and variably low, widely spread and very high due to NDV field challenge at 35 weeks of age. Based on the results, it can be concluded that all feedâs raw materials (rice bran, corn, CGM, DDGS, and SBM), the complete feed, and left over feed at Penataran Farm are contaminated by mycotoxins, including aflatoxin B1, DON, fumonisin B1, ochratoxin A, and zearalenone. The contamination of mycotoxins on the complete layer feed causing a decrease in quantity and quality of the egg.